An Error Analysis of English Plosive and Fricative Consonants at Vocational High Schools - Febby Pratama Putra (Wanastra: Jurnal Bahasa dan Sastra, 2019)
The purpose of the research is to analyze plosive and fricative consonants pronunciation errors in recordings that made by students in vocational high school in Jakarta. The research method that used to analyze plosive and fricative consonants pronunciation errors in recordings that made by the students is descriptive qualitative method and based only on a few sound recordings.